Elucidation of the roles of the carbonic anhydrase enzymes, CanA & CanB, in the physiology of Mycobacterium smegmatis - Jackson, Gabriella Teresa (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
The bacterial pathogen Mycobacterium tuberculosis (Mtb) is the causative agent of tuberculosis (TB) and one of the leading infectious causes of death globally. The success of Mtb as a pathogen depends on its ability to detect and respond to a variety of physical and chemical stresses it encounters during infection of its human host. These environmental stresses include shifts in temperature, oxygen concentration, osmolarity and nutrient availability. Mtb is, in addition, exposed to changes in pH and CO2 concentration in the intracellular and extracellular environments it inhabits, which the bacterium has to adapt to in order to ensure its growth, survival and/or persistence during infection. Carbonic anhydrases (CAs) are a widely distributed family of enzymes that catalyse the reversible hydration of carbon dioxide (CO2) to bicarbonate (HCO3−) in the reaction: CO2 + H2O ⇄ HCO3− + H+. In microbes, CA activity is important for the activity of enzymes involved in carbon fixation as well as for maintaining pH homeostasis. Mtb is known to express three CAs, encoded by the Rv3588c, Rv1284 and Rv3273 genes (canA, canB and canC, respectively). The role(s) of these CA enzymes in the physiology of Mtb and other mycobacterial species, such as Mycobacterium smegmatis (Msm), has not been elucidated to date. To gain insights into the function of the CanA and CanB enzymes in mycobacterial species, we generated both canA and canB knockdown (KD) and knockout (KO) mutants in the fast-growing mycobacterial species, Msm, and analysed their growth phenotypes under several growth conditions where CA activity is known to be required. Notably, Msm lacks the CanC homologue, which makes it an ideal surrogate to focus on CanA and CanB. The Msm canA KD mutant was found to display a growth defect following anhydrotetracycline (ATc)-mediated gene silencing at atmospheric (low) CO2 concentrations [~0.035% CO2 (v/v)]. The growth defect could be rescued by incubating cells at physiological (high) CO2 concentrations [~5% CO2 (v/v)] or by supplementing the growth media with either HCO3− or the metabolic end-products of certain HCO3−-dependent-carboxylase enzymes at low CO2 concentrations. The ability of these compounds to rescue the growth of the canA KD mutants was, however, dependent on the extent of ATc-mediated gene silencing, suggesting that the canA gene is required for Msm growth at both low and high CO2 concentrations. This was confirmed by our findings that canA could only be genetically inactivated when a second copy of the gene was provided on the chromosome in trans, regardless of the CO2 concentration used. In contrast to our observations for canA, no differences in the growth phenotypes of the Msm wild type (WT) and canB KD or knockout (KO) mutant strains were observed following silencing or inactivation of the canB gene at either low or high CO2 concentrations or different pH values. These observations suggest that, in contrast to canA, the canB gene is dispensable for the growth of Msm under standard laboratory growth conditions. The canB KO mutant strain, nevertheless, displayed a slight decrease in its ability to form biofilms when compared to the WT strain, which could be restored by genetic complementation. CanB activity may, therefore, be required to promote bacterial growth and/or survival under biofilm conditions where CO2 diffusion into cells is limited, a phenomenon that has recently been observed in other microbes. Further studies are required to confirm the role of CanB in biofilm formation and to determine how the different CA enzymes cooperate to promote the growth and survival of mycobacterial species in the various environments they are known to inhabit.
Keywords: Mycobacterium tuberculosis; Mycobacterium smegmatis; Carbonic anhydrase; CRISPR; Homologous recombination; Drug targeting